2015
DOI: 10.1177/2156587215573664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trigonella foenum graecum L on the Activities of Antioxidant Enzyme and Their Expression in Tissues of Alloxan-Induced Diabetic Rats

Abstract: Diabetes is a life-threatening metabolic disorder. This study was undertaken to evaluate the antihyperglycemic and antioxidative potential of seed powder of Trigonella foenum-graecum L in alloxan (55 mg/kg) induced diabetic rats. The results obtained showed that extensive oxidative stress is generated in tissues of diabetic rats as evidenced by increased production of hydrogen peroxide, increased accumulation of malondialdehyde (MDA) and 4-hydroxynonanal (4HNE) and decreased activities of superoxide dismutase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Trigonella foenum graecum L. (fenugreek) is being used as folk medicine for diabetes treatment and several studies have demonstrated that fenugreek seed extract, mucilage of seeds and leaves have hypoglycemic effect in experimental diabetic animals and in humans [ 44 , 45 ]. A study by Sharma and coworkers [ 46 ] showed that beside hypoglycemic effect, T. foenum graecum aqueous extract increases activities and mRNA levels of SOD, GPx and CAT in the liver and the brain of alloxan-induced diabetic rats. In another study, T. foenum graecum aqueous seed extracts lowered blood glucose levels, total cholesterol, triglycerides, and increased high density lipoprotein (HDL) cholesterol in STZ-diabetic rats.…”
Section: Plants With Antidiabetic and Antioxidant Properties Modulmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigonella foenum graecum L. (fenugreek) is being used as folk medicine for diabetes treatment and several studies have demonstrated that fenugreek seed extract, mucilage of seeds and leaves have hypoglycemic effect in experimental diabetic animals and in humans [ 44 , 45 ]. A study by Sharma and coworkers [ 46 ] showed that beside hypoglycemic effect, T. foenum graecum aqueous extract increases activities and mRNA levels of SOD, GPx and CAT in the liver and the brain of alloxan-induced diabetic rats. In another study, T. foenum graecum aqueous seed extracts lowered blood glucose levels, total cholesterol, triglycerides, and increased high density lipoprotein (HDL) cholesterol in STZ-diabetic rats.…”
Section: Plants With Antidiabetic and Antioxidant Properties Modulmentioning
confidence: 99%
“… [ 42 ] Trigonella foenum graecum Aqueous extract Liver Alloxan- diabetic rats Hypoglycemic effect; increases activities and mRNA levels of SOD, GPx and CAT. [ 46 ] Aqueous extract Circulation STZ-diabetic rats Loweres blood glucose levels, total cholesterol, triglycerides and increases HDL. [ 47 ] Ixeris gracilis DC.…”
Section: Plants With Antidiabetic and Antioxidant Properties Modulmentioning
confidence: 99%
“…Concerning the antidiabetic properties of these plants, the hypoglycemic effects of both extracts verified their ethnobotanical applications. 25,26 Aqueous extract of fenugreek seeds was capable of abolishing the elevated levels of serum malondialdehyde in a model of chronic ethanol toxicity. 27 Furthermore, the polyphenol compounds of T. foenum graecum seeds significantly decreased serum lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…31 The decreased activity of SOD and CAT could also be due to their decreased protein expression levels in the diabetic condition as reported recently in liver. 32 However, the activity of GPx and GR are enhanced in the diabetic rat brains. The result is consistent with the studies of Ulusu et al which suggest that the increased GPx and GR activity represents compensatory mechanism to degrade H 2 O 2 , which are produced in excess during the metabolism of catecholamines.…”
Section: Effect On Lipid Peroxidation Levelmentioning
confidence: 97%